2015
DOI: 10.1007/s00259-015-3070-1
|View full text |Cite
|
Sign up to set email alerts
|

Association between 18F-FDG uptake and molecular subtype of breast cancer

Abstract: SUVmax, a metabolic semiquantitative parameter, shows a significant correlation with the molecular subtype of breast cancer, and is useful for predicting the luminal A or HER2-positive subtype.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
53
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(67 citation statements)
references
References 24 publications
12
53
2
Order By: Relevance
“…In patients with recently diagnosed BC, the baseline glycolytic activity on 18F-FDG PET/CT is associated with tumor biology. Evidence level II [47][48][49][50][51][52][53][54][55][56] (Table 8). Question (f): Does the metabolic information from a baseline 18F-FDG PET/CT have implications for the patient's prognosis?…”
Section: Resultsmentioning
confidence: 99%
“…In patients with recently diagnosed BC, the baseline glycolytic activity on 18F-FDG PET/CT is associated with tumor biology. Evidence level II [47][48][49][50][51][52][53][54][55][56] (Table 8). Question (f): Does the metabolic information from a baseline 18F-FDG PET/CT have implications for the patient's prognosis?…”
Section: Resultsmentioning
confidence: 99%
“…FDG uptake, on the other hand, is correlated with molecular subtype, i.e., luminal A, luminal B (HER2-negative), luminal B (HER2-positive), HER2 positivity and triple-negativity [16,17]. Kitajima et al [17] have demonstrated that the triple-negative subtype and HER2-positive subtype show a higher SUV max , whereas the luminal A subtype often shows a lower SUV max .…”
Section: Factors Correlated With Fdg Uptake In Primary Breast Tumorsmentioning
confidence: 99%
“…Kitajima et al [17] have demonstrated that the triple-negative subtype and HER2-positive subtype show a higher SUV max , whereas the luminal A subtype often shows a lower SUV max . They also reported that a cut-off value of 3.60 yielded a sensitivity of 70 % and a specificity of 66 % for predicting that a tumor was of the luminal A subtype, and that a cut-off value of 6.75 yielded a sensitivity of 65 % and a specificity of 75 % for predicting a HER2-positive subtype.…”
Section: Factors Correlated With Fdg Uptake In Primary Breast Tumorsmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies have demonstrated a correlation between FDG accumulation on PET/CT and pathological characteristics. The maximum standardized uptake value (SUVmax) can be an independent prognostic factor, and high levels of FDG accumulation indicate more aggressive proliferation potential in breast cancers [8]- [13]. Moreover, several authors have demonstrated that FDG accumulation might be a good predictor for HER2 overexpressing and triple-negative molecular subtypes [12] [13] [14] [15].…”
Section: Introductionmentioning
confidence: 99%